Group 2 Innate Lymphoid Cells Are Involved in Skewed Type 2 Immunity of Gastric Diseases Induced by Helicobacter pylori Infection. (12th September 2017) - Li, Rong; Jiang, Xiao-xia; Zhang, Lin-fang; Liu, Xiao-ming; Hu, Ting-zi; Xia, Xiu-juan; Li, Ming; Xu, Can-xia
Abstract : H. pylori induces a complicated local and systematic immune response and contributes to the carcinogenesis of gastric cancer. A primary type 1 immune response is evoked by H. pylori since its occurrence. However, it is not unusual that an inhibitory immunity is dominant in H. pylori -associated diseases, which are promoted by the formation of immunosuppressive microenvironment. But whether group 2 innate lymphoid cells (ILC2s) plays a critical role in H. pylori -induced skewed type 2 immunity is still unclear. In the present study, firstly, we confirmed that type 1 immunity was inhibited and type 2 immunity were undisturbed or promoted after H. pylori infection in vitro and in vivo. Secondly, GATA-3 was firstly found to be increased in the interstitial lymphocytes from H. pylori -associated gastric cancer, among them, Lin−GATA-3 + cells and Lin + GATA-3 + cells were also found to be enhanced, which indicated an important role for ILC2s in H. pylori infection. More importantly, ILC2s were found to be increased after H. pylori infection in clinical patients and animal models. In conclusion, our results indicated that ILC2-mediated innate immune response might play a potential role in dominant type 2 phenotype and immunosuppressive microenvironment in H. pylori infection.